EU supply chain regulations between efficiency and effectiveness - Gabriel Felbermayr; Klaus S. Friesenbichler; Markus Gerschberger; Birgit Meyer; Peter Klimek (Austrian Institute of Economic Research (WIFO), 2025)
The newly introduced EU supply chain regulation emphasises the importance of enforcing social and environmental rules, particularly in third countries. For example, the EU's Corporate Sustainable Due Diligence Directive holds importing firms accountable for breaches in their supply chains. Following fierce criticism regarding the compliance costs of the regulation, the European Commission has amended the regulation as part of the so-called "Omnibus Package". Against this backdrop, this paper discusses the regulation, recognising that regulators must balance the trade-off between effectiveness and cost-efficiency. The Omnibus Package limits the liability of companies to the first tier. While this reduces bureaucratic costs, it also undermines the scope and effectiveness of the regulation to a greater degree. This is because many companies that are potentially in breach are likely to be active in the second and lower tiers. Nevertheless, elevated due diligence expenses and opaque supply chains act as counterarguments to a more extensive delineation of in scope companies. Adopting systemic solutions to supply chain regulation rather than idiosyncratic, non-standardised due diligence procedures would be a more effective way of addressing these issues.
Keywords: F13; F18; J80; 330; supply chain; regulation; EU; Omnibus; efficiency; effectiveness; due diligence